Prevalence of malocclusion and craniofacial morphological variations among 7-13-year-old children in Elementary School, Kediri - Triwardhani, Ari; Winoto, Ervina Restiwulan; Alida, Alida; Pramusita, Adya; Iskandar, Regina Purnama Dewi; Jordana, Jesslyn; Noor, Tengku Natasha Eleena binti Tengku Ahmad (Indonesian Journal of Dental Medicine, 2024)
Background: Craniofacial morphological variations can influence malocclusion. Mesocephalic head tends to form mesoprosopic face and class I malocclusion. Dolicocephalic head tends to form leptoprosopic face and class II malocclusion. Brachycephalic head tends to form euryprosopic face and class III malocclusion. Emphasizing the importance of malocclusion early treatment, research on malocclusion prevalence and craniofacial morphology variations in growing children is needed. Purpose: To determine malocclusion prevalence and craniofacial morphological variations among 7-13-year-old children at Medowo III Elementary School, Kediri. Methods: This descriptive study used 44 samples of Medowo III Elementary School, Kediri students. Head and face length and width were measured using a spreading caliper. The cephalic and facial indices were then determined for the classification of head and facial types. Results: The dominant craniofacial morphological variations in the samples were hyper-brachycephalic head (39 samples) and euryprosopic face (14 samples). The highest prevalence of malocclusion among individuals with hyper-brachycephalic head type was Angle’s class I malocclusion. Class II malocclusion was found in 1 sample, and class III malocclusion in 3 samples. Among the samples with this head type, the most common malocclusion variations were anterior crowding (36 samples), followed by deep bite (15 samples). Conclusion: The highest prevalence of malocclusion among Medowo III Elementary School, Kediri students was Angle class I malocclusion, characterized by specific craniofacial morphological variations, namely hyper-brachycephalic head type and euryprosopic face.